The Work Environment of the School Leader in Australia: The Case for Sustained Change in Role and Practice - Brian J. Caldwell (Education Sciences, 2024)
The questions addressed in this essay are (1) how has the work environment of school leaders changed in the early years of the 21st century, (2) how have these changes affected the role of the school leader, (3) what is the association between an evident deterioration in the work environment and the trend to more autonomy for schools and their leaders, and (4) how can school systems be more effective in supporting school leaders? The essay is organised into three domains that emerged from a review of the literature on changes in the work environment: intensification–intimidation, autonomy–accountability and system–support. Six recommendations are derived from the evidence: principals should have greater control over their work environment, system leaders should remove many reporting requirements from schools, there should be “organised abandonment” of outdated practices, the potential benefits of AI should be realised, there should be more engagement in planning for the future, and there should be further research on processes and outcomes through randomised controlled trials of new practices. It is not so much new theories in leadership but rather new roles and new practices within different arrangements for governance, informed by ongoing research as the context changes, amid evidence of deterioration in professional wellbeing.